2013
DOI: 10.1007/s00125-012-2810-z
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-time physical activity is a significant predictor of stroke and total mortality in Japanese patients with type 2 diabetes: analysis from the Japan Diabetes Complications Study (JDCS)

Abstract: Aims/hypothesis Our aim was to clarify the association between leisure-time physical activity (LTPA) and cardiovascular events and total mortality in a nationwide cohort of Japanese diabetic patients.Methods Eligible patients (1,702) with type 2 diabetes (mean age, 58.5 years; 47% women) from 59 institutes were followed for a median of 8.05 years. A comprehensive lifestyle survey including LTPA and occupation was performed using standardised questionnaires. Outcome was A complete list of members of the JDCS gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 45 publications
3
46
1
1
Order By: Relevance
“…In the Japan Diabetes Complications Study (JDCS), an analysis of leisure-time activity in 1702 participants with type 2 diabetes (based on HbA1c≥6.5 %) aged 40-70 years from 59 clinics and hospitals found that after a median of 8 years, leisure-time activity was associated with total mortality (HR 0.49, 95 % CI 0.26-0.91) but not fatal heart disease, when comparing the top tertile (≥15.4 metabolic equivalents [METs, hours/week]) versus the bottom tertile (≤3.7 MET [hours/week]), adjusted for age, sex, and diabetes duration. Also, no significant difference was found between tertiles 2 and 1 [30].…”
Section: Mortalitycontrasting
confidence: 49%
See 2 more Smart Citations
“…In the Japan Diabetes Complications Study (JDCS), an analysis of leisure-time activity in 1702 participants with type 2 diabetes (based on HbA1c≥6.5 %) aged 40-70 years from 59 clinics and hospitals found that after a median of 8 years, leisure-time activity was associated with total mortality (HR 0.49, 95 % CI 0.26-0.91) but not fatal heart disease, when comparing the top tertile (≥15.4 metabolic equivalents [METs, hours/week]) versus the bottom tertile (≤3.7 MET [hours/week]), adjusted for age, sex, and diabetes duration. Also, no significant difference was found between tertiles 2 and 1 [30].…”
Section: Mortalitycontrasting
confidence: 49%
“…Similarly, leisure-time exercise METs in the JDCS study were not significantly associated with nonfatal coronary heart disease [30]. In JDCS, the hazard ratio for stroke was protective (HR 0.55, 95 % CI 0.32-0.94) after adjustment for age, sex, and diabetes duration but was not statistically significant after additional adjustments for lifestyle and clinical variables such as diet and serum lipids (HR 0.56, 95 % CI 0.26-1.20) [30].…”
Section: Nonfatal Myocardial Infarction and Strokementioning
confidence: 81%
See 1 more Smart Citation
“…8 A cohort study of individuals with newly diagnosed diabetes mellitus, followed up for 5 years, found that those who increased their PA had a relative risk of total cardiovascular disease (including stroke and myocardial infarction) of 0.53 compared with those who decreased their PA. 51 When considering the association between stroke and PA in people with diabetes mellitus, those who participated in at least 30 minutes/d of brisk walking, or the equivalent, had a 45% reduction in stroke risk compared with those who were inactive. 52 Several different variables are used in studies to classify excess weight: measurement of body mass index, waist circumference, waist:hip ratio, visceral adipose tissue, and overall body fat. Randomized controlled trials of PA interventions typically result in only modest weight loss (1-2 kg), 5 but they are often associated with improvements in body mass index, waist circumference, and body fat with PA interventions, 46 particularly in those with diabetes mellitus.…”
Section: How Does Pa Modify the Risk Factors For Stroke?mentioning
confidence: 99%
“…Otro estudio 52 analizó el beneficio de realizar altos niveles de actividad física sobre el riesgo de presentar un evento vascular cerebral, reportando que un volumen de actividad física mayor a 15.4 MET/Hora/semana de actividad física se asocia a una disminución del riesgo relativo del 45% (HR 0.55, IC95% 0.32 a 0.94) de presentar un evento vascular cerebral; sin embargo esta asociación no fue significativa para la enfermedad coronaria (HR 0.77, IC95% 0.48 a 1.25).…”
Section: Impacto Clínico De La Actividad Física En El Tratamiento Y Cunclassified